2017
DOI: 10.1021/acs.biochem.7b00219
|View full text |Cite
|
Sign up to set email alerts
|

Acyl Carrier Protein Cyanylation Delivers a Ketoacyl Synthase–Carrier Protein Cross-Link

Abstract: Acyl carrier proteins (ACPs) are central hubs in polyketide and fatty acid biosynthetic pathways, but the fast motions of the ACP’s phosphopantetheine (Ppant) arm make its conformational dynamics difficult to capture using traditional spectroscopic approaches. Here we report that converting the terminal thiol of E. coli ACP’s Ppant arm into a thiocyanate activates this site to form a selective crosslink with the active site cysteine of its partner ketoacyl synthase (KS; FabF). The reaction releases a cyanide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 17 publications
5
18
0
Order By: Relevance
“…ACPs were expressed and purified as described previously. 27 In brief, ACP expression plasmids were transformed into chemically competent BAP1 cells for expression. 28 Seed cultures (10 mL LB, 50 μg kanamycin/mL or 100 μg/mL carbenicillin) were grown at 37 °C with shaking and then added to 1 L LB production cultures (50 μg kanamycin/mL or 100 μg/mL carbenicillin).…”
Section: Methodsmentioning
confidence: 99%
“…ACPs were expressed and purified as described previously. 27 In brief, ACP expression plasmids were transformed into chemically competent BAP1 cells for expression. 28 Seed cultures (10 mL LB, 50 μg kanamycin/mL or 100 μg/mL carbenicillin) were grown at 37 °C with shaking and then added to 1 L LB production cultures (50 μg kanamycin/mL or 100 μg/mL carbenicillin).…”
Section: Methodsmentioning
confidence: 99%
“…We later reported that converting the terminal thiol of the Ppant arm to a thiocyanate provides a site-specific vibrational spectroscopic probe for ACPs that reports on the Ppant arm conformational dynamics of the ACP itself 5 . In the presence of a compatible KS, the thiocyanate-labeled ACP is activated to form a mechanistically relevant cross-link through disulfide bond formation between the Ppant arm thiol and partner KS thiolate 6 . The concomitant release of CN − enables the monitoring of ACP-KS interactions via infrared (IR) spectroscopy (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Each student designed, constructed, expressed and purified a distinct mutant ACP to convert to the thiocyanate version and assess via mechanistic cross-linking. In addition, students expressed and purified wild type AcpP as a positive control along with the ACP from the actinorhodin type II PKS (ACT ACP) as a negative control since this protein does not bind to FabF in vitro 68 . One student observed that their reaction turned yellow upon mixing their thiocyanate-labeled AcpP mutant with the KS.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the dynamic nature of both the protein and PPant 10 , AcpP can sequester diverse cargo lengths and moieties with important cargoinduced structural and regulatory consequences 11 . Synthetic cargo attachment offers an excellent handle for structural biology studies 12,13 . During interaction with partner proteins, the cargo completely translocates from the hydrophobic core of AcpP into the partner in a process called "chain flipping" 14,15 .…”
mentioning
confidence: 99%